Artificial Intelligence in EFL Reading Instruction: A Systematic Literature Review - Sylvia (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The integration of Artificial Intelligence (AI) into English as a Foreign Language (EFL) teaching represents a significant shift in the evolution of contemporary literacy education. While AI has been extensively researched in speaking and writing, its pedagogical application in reading instruction remains relatively under-researched. This systematic literature review was conducted by synthesizing empirical research published in 2025, 2024 and 2023 that investigated the use of AI-based tools and platforms in EFL reading contexts. Based on a collection of journal articles that have been reviewed, the results of the review include pedagogical implementation of artificial intelligence in EFL reading instruction, current developments in the use of artificial intelligence in EFL reading instruction, empirical findings from previous studies, research gaps, practical and theoretical directions for the use of artificial intelligence in EFL reading instruction and recommendations for future research. The findings are that AI helps to improve students' reading motivation, learner engagement, reading performance, learner autonomy, cognitive and emotional engagement, task performance, inferencing skills and self-regulated learning. Undoubtedly, there are many things that need to be considered in the use of AI, such as technological accessibility, individual learner differences, ethical concerns and teacher preparedness. Then, the results of the analysis of previous research recommend the need for teacher training, important implications for learning design, and future research directions that view AI as a transformational catalyst in EFL reading education.